Cavo-atrial thrombectomy prior to hepatectomy for hepatocellular carcinoma with tumor thrombus in the right atrium: a case report - Shun-ichi Ariizumi; Chizuo Kikuchi; Fumiaki Tokitou; Shingo Yamashita; Yoshihito Kotera; Akiko Omori; Takaaki Kato; Satoshi Nemoto; Hiroshi Niinami; Masakazu Yamamoto (Surgical Case Reports)
Abstract Background Hepatocellular carcinoma (HCC) with tumor thrombus (TT) in the right atrium is a critical condition. The general consensus is to perform hepatectomy prior to cavo-atrial thrombectomy because of the risk of uncontrollable bleeding during the liver transection after heparinization. However, sudden cardiac arrest due to the ball-valve effect and pulmonary embolism have been reported in cases of TT. Cavo-atrial thrombectomy prior to hepatectomy for HCC with TT in the right atrium was successfully performed to prevent sudden cardiac arrest and pulmonary embolism. Case presentation Tumor thrombectomy under cardiopulmonary bypass with heparin and electrical ventricular fibrillation prior to hepatectomy was successfully performed to prevent sudden cardiac arrest or pulmonary embolism in a 75-year-old woman with a huge HCC and TT in the right atrium. After the neutralization of heparin, right hepatectomy with tumor thrombectomy in the inferior vena cava was performed. The total operation time was 9 h, and the total blood loss was 8200 mL. The patient’s postoperative course was uneventful, and she was discharged 14 days after surgery. One year after surgery, she is alive with HCC recurrence in the lung. Conclusions Cavo-atrial thrombectomy prior to hepatectomy for HCC with TT in the right atrium can be performed safely to prevent sudden cardiac arrest and pulmonary embolism by collaboration of cardiovascular surgeons and gastroenterological surgeons.